2014
DOI: 10.1177/0956797614553947
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Status Shapes Political Preferences

Abstract: Economic inequality in America is at historically high levels. Although most Americans indicate that they would prefer greater equality, redistributive policies aimed at reducing inequality are frequently unpopular. Traditional accounts posit that attitudes toward redistribution are driven by economic self-interest or ideological principles. From a social psychological perspective, however, we expected that subjective comparisons with other people may be a more relevant basis for self-interest than is material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
138
2
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(162 citation statements)
references
References 36 publications
13
138
2
9
Order By: Relevance
“…In line with this, there is evidence that those who are at the top of the wealth hierarchy are more tolerant of inequality than those at the bottom [35]. Indeed, recent research has shown that wealthier individuals are more likely than poorer individuals to be motivated to maintain inequality [36].…”
Section: Groups Within Society Are Likely To Differ In How They Respomentioning
confidence: 90%
“…In line with this, there is evidence that those who are at the top of the wealth hierarchy are more tolerant of inequality than those at the bottom [35]. Indeed, recent research has shown that wealthier individuals are more likely than poorer individuals to be motivated to maintain inequality [36].…”
Section: Groups Within Society Are Likely To Differ In How They Respomentioning
confidence: 90%
“…Specifically, the motivation to believe that one's elevated position in society is both fairly achieved and possible for all Americans will lead individuals from relatively upper-class backgrounds to make larger overestimates of social class mobility. Several lines of research support this perspective: for instance, people with higher status are happier when they believe that positive outcomes in society are based on merit (Napier & Jost, 2008;O'Brien & Major, 2005) and highperforming members of a group are more likely to advocate dividing resources based solely on merit (Brown-Iannuzzi, Lundberg, Kay, & Payne, 2015;Messick & Sentis, 1979). As well, individuals who ranked themselves more highly in subjective social class reported a greater belief that the world is both meritocratic and that economic outcomes are fair than did their lower-class counterparts (Kraus & Keltner, 2013).…”
Section: Social Class and Estimates Of Class Mobilitymentioning
confidence: 98%
“…In the present research, we use correlational (Studies 1 and 3) and experimental (Study 4) approaches to explore and estimate the precise direction and strength of the relationship between measures of social class and estimates of class mobility. Moreover, it is possible that distinct components of social class will be differentially related to overestimates of class mobility (Kraus, Piff, Mendoza-Denton, Rheinschmidt, & Keltner, 2012)-with education being negatively related given its relationship to information exposure, and subjective rank perceptions of social class being positively related, given associations with meritocracy judgments in prior research (Brown-Iannuzzi et al, 2015). Because of these conditions, throughout the studies we separately examine relationships between unique facets of social class and class mobility beliefs.…”
Section: Social Class and Estimates Of Class Mobilitymentioning
confidence: 99%
“…Similarly, upper class and high-power individuals tend to be less generous and charitable and more likely to take valued goods from others, behaviors that indicate that they are less willing to share their resources (Dubois, Rucker, & Galinsky, 2015;Lammers, Stapel, & Galinsky, 2010;Piff, Kraus, Côté, Cheng, & Keltner, 2010;Piff, Stancato, Côté, Mendoza-Denton, & Keltner, 2012;Rucker, DuBois, & Galinsky, 2011). Likewise, higher socioeconomic-status (SES) individuals show less support for redistributive policies that aim to reduce social inequality (Brown-Iannuzzi, Lundberg, Kay, & Payne, 2015) and restorative justice interventions that intend to enhance social opportunity (Kraus & Keltner, 2013).…”
Section: Verticality Norm Violators and Maintenance Of Hierarchymentioning
confidence: 99%